Development and reliability of countermovement jump performance in youth athletes at pre-, circa- and post-peak height velocity - Bright, T.; Handford, M. J.; Hughes, J. D.; Mundy, P. D.; Lake, J. P.; Doggart, L. (International Journal of Strength and Conditioning, 2023)
The purpose of this study was to determine the intrasession reliability of countermovement jump (CMJ) braking and propulsive phase variables in youth athletes. Thirty youth athletes between the age of 10- and 16-years volunteered to take part in this study. All participants performance 3 CMJ trials on a force platform. Thirteen of 16 CMJ variables were found to have acceptable absolute reliability in the pre-PHV group (CV% = 3.51-9.96) whilst the circa-PHV group contained 10 variables demonstrating acceptable absolute reliability (CV% = 2.37-9.67). Almost all variables (14 out of 16) in the post-PHV group were found to have acceptable absolute reliability (CV% = 2.59-9.61). Mean and peak braking RFD displayed poor absolute reliability in all maturity groups (CV% = 10.89-21.55). Time to take-off, braking and propulsive phase time and propulsive impulse demonstrated the largest differences between pre- and circa-PHV groups (p < 0.005; d > 0.95). Braking phase time, peak and mean braking force, mean braking power and RSImod demonstrated the biggest differences between the circa- and post-PHV groups (p < 0.001; d > 1.81). The poorest reliability scores were found in the circa-PHV group, demonstrating the need for additional familiarisation at this stage of maturity.